Can hospitals impact users' experience? Application of an evaluation tool to enhance Design for All. (20th October 2021) - Mosca, EI; Steinfeld, E; Capolongo, S
Abstract: Background: Design for All (DfA) strategy addressing human diversity, social inclusion and equality, can have an impact on users' well-being in healthcare facilities. However, evaluation tools are needed to identify the extent to which DfA influences users' experience and service quality. This study explores the application of the Design for All A.U.D.I.T. (Assessment Usability Design & Inclusion Tool). Methods: The tool's structure is based on a multicriteria framework that evaluate hospital areas through a rating system. The hierarchical framework includes three Categories of DfA outcomes (Physical-spatial quality; Sensorial-cognitive quality and Social quality) with related criteria, indicators and requirements. The tool has been applied in the evaluation of two private hospitals, one in Buffalo (US) and one in Milan (Italy). Results: The analysis of findings addressed both spatial and DfA qualities. For spaces, Horizontal circulation had the best scores in both hospitals (76% Italy, 88% US). The Italian hospital Vertical circulation had the lowest score (46%), while in the Buffalo facility Outdoor spaces had the lowest scores. Regarding DfA qualities, the Italian hospital obtained the highest score in Environmental Factors (84%), due to a sustainable design approach, while Social Inclusion got the lowest score (54%). The Buffalo facility scored higher on Social Inclusion (87%) because it provides diverse services for users. Both the hospitals had problems with Wayfinding due to layout and signs, scoring low on this criterion (59% Italy, 39% US). Conclusions: The analysis of the hospitals demonstrated that the tool can evaluate spaces and DfA outcomes along dimensions of health and well-being. The system can be used to identify critical aspects and suggest design strategies, defining priorities for interventions. Further research directions will consider applications in different hospitals to ensure the tool scalability and application to new building projects. Key messages: The evaluation tool enhances Public Health by measuring hospital quality in terms of Design for All and user needs. The tool can be applied in the decision-making process during design and renovation of specific areas of hospitals to implement Inclusive Design.